The Success of Viral Videos on YouTube as a Growth Driver for MSMEs (Micro, Small, and Medium Enterprises) - Moh. Ilham; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Viral videos on YouTube have become an important source in the growth of Micro, Small and Medium Enterprises (MSMEs). This research aims to analyze 12 viral YouTube message videos with views above 1 million in the context of MSMEs (using the hashtag #UMKM). An in-depth literature review is used to understand the theoretical basis of the viral video phenomenon and how it can be an effective instrument in supporting MSME business growth. Research methods include analysis of video content, including elements that lead to virality, impact on brand awareness, and increased sales. The results of this research reveal important messages, such as creativity, emotional appeal, the use of appropriate keywords, and a positive impact on the growth of MSMEs.